PERGESERAN STRUKTUR EKONOMI DAERAH: SEBUAH ANALISA EKONOMI DI KABUPATEN CIREBON - Agus Prabawa; Zumaeroh Zumaeroh (FEB UNWIKU PURWOKERTO, 2020)
The economic development of a region cannot be separated from how the region is able to optimize all its resources effectively and efficiently. Cirebon Regency as one of the strategic areas in West Java Province has a tendency to change its economic structure. Based on this, this study seeks to determine the economic structure in Cirebon Regency and its shifting trend. By using regional macroeconomic data which is then analyzed with several models such as SLQ analysis, DLQ, and Klassen typology with SPSS software. Based on the analysis, it is known that the Cirebon Regency economy has experienced a shift from the primary economic sector to the secondary and tertiary economic sectors where 20.68% is generated from the contribution of the manufacturing industry. Based on the results of the Klassen Typology analysis which combines the data from the analysis of the SLQ and DLQ models, it is known that there are six economic sectors in Cirebon Regency that are experiencing growth and are the basic sectors, namely: education services, corporate services, financial services and insurance, transportation and warehousing, agriculture, forestry and livestock, as well as water supply. These results indicate that Cirebon Regency can develop an industrial sector based on agricultural and plantation commodities in order to be able to create a sustainable industrial pattern from the upstream sector to the downstream sector. It is felt that this industrial pattern will be more able to have a positive economic impact and be felt directly by the community.